C‐C Chemokine Receptor Type 5 (CCR5)‐Mediated Docking of Transferred Tregs Protects Against Early Blood‐Brain Barrier Disruption After Stroke - Peiying Li; Long Wang; Yuxi Zhou; Yu Gan; Wen Zhu; Yuguo Xia; Xiaoyan Jiang; Simon Watkins; Alberto Vazquez; Angus W. Thomson; Jun Chen; Weifeng Yu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundDespite recent evidence demonstrating a potent protective effect of adoptively transferred regulatory T cells (Tregs) in ischemic stroke, the mechanism for Treg mobilization and activation in the ischemic brain is, remarkably, unknown. This study determines the role of C‐C chemokine receptor type 5 (CCR5) in mediating the docking and activation of transferred Tregs in their protection of early blood‐brain barrier disruption after stroke. Methods and ResultsAdoptive transfer of CCR5−/− Tregs failed to reduce brain infarct or neurological deficits, indicating an indispensable role of CCR5 in Treg‐afforded protection against cerebral ischemia. Two‐photon live imaging demonstrated that CCR5 was critical for Treg docking at the injured vessel wall, where they interact with blood‐borne neutrophils/macrophages after cerebral ischemic injury. CCR5 deficiency on donor Tregs deprived of their early protection against blood‐brain barrier damage. Using flow cytometry, real‐time polymerase chain reaction, and immunostaining, we confirmed that the expression of CCL5, a CCR5 ligand, was significantly elevated on the injured endothelium after cerebral ischemia, accompanied by CCR5 upregulation on circulating Tregs. In a Treg‐endothelial cell coculture, CCR5 expression was induced on Tregs on their exposure to ischemia‐injured endothelial cells. Furthermore, CCR5 induction on Tregs enhanced expression of the inhibitory molecule programmed death ligand 1, which in turn inhibited neutrophil‐derived matrix metallopeptidase 9. ConclusionsThese results suggest that CCR5 is a critical molecule for Treg‐mediated blood‐brain barrier protection and a potential target to optimize Treg therapy for stroke.